Mechanochromic luminogen with aggregation-induced emission: implications for ink-free rewritable paper with high fatigue resistance and low toxicity. Issue 35 (19th August 2016) - Sun, Jingyan; Han, Jingqi; Liu, Yang; Duan, Yuai; Han, Tianyu; Yuan, Jing
Abstract : Paper can be made rewritable using a new mechanochromic luminogen. Abstract : In this study, we report the synthesis and photoluminescence (PL) behaviour of a new luminogen, DHBA, a functionalized Schiff base. The twisted molecular conformation together with the incorporation of electron donor–acceptor pairs endow the luminogen with both aggregation-induced emission and twisted intramolecular charge transfer properties. The crystalline luminogen shows strong green emission at around 514 nm while the emission colour turns orange-red (562 nm) with a big loss in the quantum efficiency after grinding. The colour of the ground sample can be readily converted back into the initial state though recrystallization by either immersing or fuming in organic solvents. The conversion can be implemented for more than 30 cycles, showing good repeatability. This luminogen probably shows the highest fatigue resistance among all the mechanochromic compounds that have been reported. Inspired by the unique mechanochromism, an archetype of ink-free rewritable paper is developed. Letters and patterns can be easily written using pressure and erased by fumigation in handwriting experiments. The luminogen also enjoys the advantages of a one-pot synthesis and low biotoxicity, providing a reliable candidate for green rewritable paper technology to fulfill demands for sustainability and carbon mitigation.